Aplikasi Scheduler Team Meeting Berbasis Mobile Dengan Menggunakan Push Notification - Masmur Tarigan; Adven Kristianata (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
Each team / individual in a company has its own internal and external meetings. At present PT NTX Solusi Teknologi does not have a system that can schedule meetings and track its employees who carry out meetings, it affects the time management for each individual or team that collaborates with each other. The purpose of making this application is for scheduling, notification of meetings, monitoring the team that is conducting the meeting, and also for data collection by the company admin. Because employees use a variety of devices, applications are created using Web Responsive that can adjust the appearance of employee devices and have the same functionality for all devices. The method used in making this application is the Prototype method for gathering needs, designing and evaluating programs. The problem analysis method uses Fishbone analysis to obtain specific problems. The program will be tested with the Black Box method to ensure the system runs well. With this conclusion the scheduler application can be used to make the schedule, tracking members who carry out external meetings, used by various devices and has a responsive display. And based on testing Black Box the application can run well.